Development of 3-phase fault detection, protection, and automation application with the present of DG in AC power system using GOOSE protocol - Zhongsheng Shi; Zumrat Druzhinin (Heliyon, 2024)
In this research work, a protection and automation solution is developed, encompassing SEL751 and SEL751A protection relays that communicate through the IEC-61850 Generic Object-Oriented Substation Event (GOOSE) protocol to deliver high-speed detection and clearance of a 3-phase (3P) fault. The study case is a standard IEEE 13-bus grid including the main system generator (G1), power lines, loads, distributed generation (DG), bus bars, and feeders, equipped with protection relays for detecting over-current faults based on time and current. Two protection relays, B1 in the main system and B2 on the DG side, are integrated with a GOOSE protocol communication system. These settings are configured in such a way that, in the event of the main system breaker being disconnected, the DG cannot be connected to the network, making it a suitable setting for anti-islanding mode (AIM). The efficiency of the relay settings is tested by subjecting the power grid to a 3P fault, by the selected Time-Overcurrent (TOC) U3 inverse curve. Throughout the paper, the descriptions of the study, the grid, assumptions, settings calculations, and analysis of results are systematically presented. For the verification of relay settings, the performance of relays is practically tested and accurately analyzed in detail. The results obtained indicate that the presented strategy is quite effective for the configuration, setting operation, and coordination of relays for fast detection and communication through the GOOSE protocol.